2019
DOI: 10.1021/acs.langmuir.9b03366
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Peptide Functionalized Gold Nanopolyhedrons with Excellent Chiral Optical Properties

Abstract: Because of the unique optical properties of gold nanomaterials, the preparation of gold nanomaterials with excellent chirality has received extensive attention. In order to develop a simple fabrication method for three-dimensional chiral Au nanostructures with a size of several hundred nanometers, chiral gold nanoparticles were developed to transfer chirality of a peptide to gold nanoparticles. In this study, the controlled synthesis of asymmetric gold nanopolyhedrons was achieved. The asymmetric gold nanopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…This indicated that SPPs had a significant field enhancement effect under incident light, which enhanced the CD effect of the prepared nanododecahedral-peptide. [52] Fang et al synthesized AuNPs/GO nanocomposites and tested their catalytic properties. In the presence of NaBH 4 , they selected 4-NP to be reduced to 4-AP.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that SPPs had a significant field enhancement effect under incident light, which enhanced the CD effect of the prepared nanododecahedral-peptide. [52] Fang et al synthesized AuNPs/GO nanocomposites and tested their catalytic properties. In the presence of NaBH 4 , they selected 4-NP to be reduced to 4-AP.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…Circular dichroism spectra of Au nanododecahedrons, peptide and Au nanododecahedrons-peptide particles (f). [52] Reprinted with permission from [52]. Copyright 2019 American Chemical Society.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…It has been known that the excitation of surface plasmons resonance will produce oscillating dipole elds due to the semicircle nanostructure with small diameters compared with the incident wavelength of the different CP lights [48][49]. When RCP or LCP light illuminate onto the semicircle nanostructure, it can be reasonably believed that the selective absorption and giant CD effect will emerge in the proposed CMSA and consequently resutling in the different distribution of the electric eld and magnetic eld components in each layer [49][50][51][52][53][54]. It can be observed that the electric dipole power is much stronger than the magnetic one in the designed semicircle nanostructure, revealing the predominance of electric dipole oscillations.…”
Section: Resultsmentioning
confidence: 99%
“…The excitation of surface plasmons resonance will produce oscillating dipole elds due to the semicircle nanostructure with small diameters relative to the incident wavelength of the different CP lights [43][44][45][46]. When RCP or LCP light excites the semicircle nanostructure, a chiral-selective absorption and giant CD effect will occur, and the electric eld and magnetic eld components of each layer are different due to the chirality [46][47][48][49][50][51]. charges are separated and mainly accumulated at the corners of the each semicircle nanostructure, acting like an electric dipole.…”
Section: Resultsmentioning
confidence: 99%